2000
DOI: 10.1029/1999ja000334
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐Magnetospheric Plasma Propulsion: Tapping the energy of the solar wind for spacecraft propulsion

Abstract: Abstract. Mini-Magnetospheric Plasma Propulsion is a potentially revolutionary plasma propulsion concept that could enable spacecraft to travel out of the solar system at unprecedented speeds of 50 to 80 km s '1 or could enable travel between the planets for low power requirements of --1 kW per 100 kg of payload and ~ 0.5 kg fuel consumption per day for acceleration periods of several days to a few weeks. The high efficiency and specific impulse attained by the system are due to its utilization of ambient ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 15 publications
6
127
2
Order By: Relevance
“…Finally η = 0 represents a constant propulsive acceleration, or a thrust that is independent of the distance from the massive attractor. Actually η = 0 is consistent with a situation in which the propulsion system is either a minimagnetospheric plasma thruster (Winglee et al, 2000;Trask et al, 2004;Mengali and Quarta, 2006), or an electric thruster when the thrust is modulated such as to provide a constant thrust-to-mass ratio (Prussing and Coverstone, 1998;Mengali and Quarta, 2009a) and the power source is independent of the Sun-spacecraft distance, as in a nuclear-powered system. This happens, for example, when the power subsystem is represented by a radio-isotope thermoelectric generator (Hunt, 1993;Lyngvi et al, 2007).…”
Section: Power Radial Thrustmentioning
confidence: 58%
“…Finally η = 0 represents a constant propulsive acceleration, or a thrust that is independent of the distance from the massive attractor. Actually η = 0 is consistent with a situation in which the propulsion system is either a minimagnetospheric plasma thruster (Winglee et al, 2000;Trask et al, 2004;Mengali and Quarta, 2006), or an electric thruster when the thrust is modulated such as to provide a constant thrust-to-mass ratio (Prussing and Coverstone, 1998;Mengali and Quarta, 2009a) and the power source is independent of the Sun-spacecraft distance, as in a nuclear-powered system. This happens, for example, when the power subsystem is represented by a radio-isotope thermoelectric generator (Hunt, 1993;Lyngvi et al, 2007).…”
Section: Power Radial Thrustmentioning
confidence: 58%
“…• First, suggestions have been made about the use of the solar wind as an energy source for spacecraft propulsion, such as the "mini-magnetosphere plasma propulsion (M2P2)" idea (Winglee et al 2000). In this approach, plasma injected into a magnetic field produced on a spacecraft plays the role of a mini-magnetosphere.…”
Section: Planetary Space Weather Impacts On Planetary Missionsmentioning
confidence: 99%
“…The propulsive force considered in this paper is minimagnetospheric plasma propulsion (M2P2), a technology proposed by Winglee et al 8) Although the full proof of the technology has yet to be reported, M2P2 is a promising propulsion technology for accelerating spacecraft in the outward radial direction.…”
Section: Introductionmentioning
confidence: 99%